PRMT5 promotes cell proliferation by inhibiting BTG2 expression via the ERK signaling pathway in hepatocellular carcinoma. (14th February 2018) - Jiang, Hai; Zhu, Yue; Zhou, Zhenyu; Xu, Junyang; Jin, Shaowen; Xu, Kang; Zhang, Heyun; Sun, Qing; Wang, Jie; Xu, Junyao
Abstract: Increasing evidence suggests that PRMT5, a protein arginine methyltransferase, has roles in cell growth regulation and cancer development. However, the role of PRMT5 in hepatocellular carcinoma (HCC) progression remains unclear. Here, we showed that PRMT5 expression was frequently upregulated in HCC tissues, and its expression was inversely correlated with overall survival in HCC patients. PRMT5 knockdown markedly inhibited in vitro HCC proliferation and in vivo tumorigenesis. We revealed that the mechanism of PRMT5‐induced proliferation was partially mediated by BTG downregulation, leading to cell cycle arrest during the G1 phase in HCC cells. Ectopic BTG2 overexpression decreased HCC growth, caused cell cycle arrest at the G1 phase, and downregulated Cyclin D1 and Cyclin E1 protein expression. Furthermore, we found that PRMT5‐induced ERK phosphorylation regulated BTG2 expression in HCC cells, whereas pretreatment with a selective ERK1/2 inhibitor (PD184352) significantly reversed the effect of PRMT5 on BTG2 expression. Our results indicated that PRMT5 promotes HCC proliferation by downregulating BTG2 expression via the ERK pathway. Abstract : Our results showed that PRMT5 expression was frequently upregulated in HCC tissues, and its expression correlated inversely with overall survival of HCC patients. Knockdown of PRMT5 markedly inhibited HCC cell proliferation in vitro and tumorigenesis in vivo. PRMT5 promoted HCC cell proliferation by downregulating BTG2 expression via ERK pathway.